Spreads microbiology in association with product matrix, structure and chemistry - Khan, Intisar Chowdhury (2015)
The overall aim of this study was to eliminate the root cause of the ‘cheese flavour’ in spread caused by four key microbes Bacillus spp, Staphylococcus spp, yeasts and moulds. The major sources of these bacteria were in the product ingredients mainly sweet cream buttermilk and skimmed milk along with environmental aerosols. The causative organisms were present in about 63% of the products and mainly ‘feed’ on the oil element of the recipe, containing high level C12 that generates the distinctive cheese flavour when broken down by bacteria.